Poverty, Health, and Safety Nexus: A Study on Child Labor in Hotels and Restaurants of Mahendranagar, Kanchanpur - Bam, Nirmala Kumari (Journal of Durgalaxmi, 2025)
This research studies the intersections of poverty, health and safety in 50 child workers aged 5-20 years in the hospitality sector in Mahendranagar, with a mixed-method study to delve into the socioeconomic situations of the child workers, health risks and rehabilitation needs. The findings indicated that most of the child workers in the study were boys (80%) between the ages of 11 and 17 years, with over half of the child workers belonging to the Tharu community (54%). Educational history was also unremarkable: 28 percent were illiterate, and 12 percent received only secondary education; poverty was the primary reason for a school drop-out (62%). With regards to health, health problems were common among children who were working: 44 percent were in poor health (oftentimes headaches, chest infections, and injuries). In terms of health, one-third reported working long hours (9-12 hours a day) and 22 percent experienced harassment, while the other 22 percent indicated there was no personal safety equipment. One-third of the children had ease of access to health services. Despite these challenges, 40 percent of the children indicated that they would return to school, and 28 percent would rather receive vocational training. An overall conclusion is that poverty remains the primary driver of child labor in the hospitality sector in Mahendranagar, working at the expense of children's safety and well-being. There is an urgent need for simple to strengthen policy implementation, address poverty and introduce rehabilitation services.